Think Pairs Share Using Concept Map (TPS UCM) untuk Meningkatkan Keterampilan Komunikasi Siswa - Triana Atika Zulfa (Departement of Mathematics Education, 2023)
This research aimed to modify the learning model of Think Pairs Share (TPS) to enhance the communication skill. This research was R & D design that modified the element of TPS with oral communication aspects and writing skills. The modification procedure used Borg & Gall: 1) observing and gathering the information, 2) planning and developing the first draft of product, 3) expert validation, and 4) try-out of the product. The data analysis that was used was qualitative and quantitative research. The result of TPS modification were; 1) the expert judgment showed 82,5% of prototype model as the researchers hoped, 87,0% fulfilled the model content, and 98,7% can be applied in the teaching and learning process. The result of the expert judgment showed that the modification model was suitably valued by the students; 2) the result of the students’ assessment showed the average of 84,2% and it can be applied in teaching and learning process; 4) the modification model called as Think Pairs Share Using Concept Map (TPS UCM).